Recurrent Erythema Multiforme. - Ekanem EE; Asindi AA. (Nigerian Journal of Paediatrics, 2024)
Summary: The case of a three-and-half-year old male child with the severe form of erythema multiforme (EM) major (Stevens-Johnson syn drome) is described. From the past medical history, the child had seven previous attacks of a similar disease in the immediate past 24 months. The first four attacks of the disease were considered, by their description, to be mild EM minor, as the lesions were limited to the skin, while the next four recurrences, including the present one, were regarded as severe, with extensive involvement of the skin, mucosae of the mouth, nose, eyes and urethral orifice, that required hospitalization. Each recurrent episode of the disease was causally related to self-medication with pyrimethamine-sulfadoxine (Fansidar). With the current frequent and indiscrimi nate use of Fansidar and other sulphonamide-containing substances as alternatives for chloroquine-resistant malaria, physicians should be alerted to the possibility of an upsurge in the prevalence and recurrent attacks of EM, minor or major, in malaria-endemic areas of the developing world.